The Role of the Indirect Internship Tutor: training needs and future perspectives - Gragnaniello, Deborah; Iannotta, Iolanda Sara (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
In a university in southern Italy, a research‐training initiative was launched to explore the role of tutors in indirect internship activities, as part of the master’s degree program in Primary Education Sciences. The research, conducted following the principles of a mixed‐methods approach, involved an initial qualitative phase and a subsequent quantitative phase. The following contribution presents the results of the second phase, which involved administering a structured questionnaire to the entire population of student interns to gather data on their opinions regarding the internship activities. The descriptive analysis of the data provides a complex picture. On one hand, the results indicate that, at the organizational level, the internship activities were structured accurately and in line with regulatory guidelines. On the other hand, there is a discrepancy between what was planned and what was implemented in practice. Specifically, the student interns reported a lack of personalized training pathways and limited opportunities to engage with diverse teach‐ing situations. The triangulation of quantitative and qualitative data (obtained during the first phase of the research) and specialized literature suggests the need for a training intervention aimed at enhancing the skills of organizational and coordinating tutors. The need emerges for in‐service training aimed at bridging the gap between theory and practice, fostering the development of relational, communication, and instructional design skills in response to the needs of the involved stakeholders.